Impact of Deleterious Mutations on Structure, Function and Stability of Serum/Glucocorticoid Regulated Kinase 1: A Gene to Diseases Correlation - AlAjmi, Mohamed F.; Khan, Shama; Choudhury, Arunabh; Mohammad, Taj; Noor, Saba; Hussain, Afzal; Lu, Wenying; Eapen, Mathew Suji; Chimankar, Vrushali; Hansbro, Philip M; Sohal, Sukhwinder Singh; Elasbali, Abdelbaset Mohamed; et al. (Frontiers in Molecular Biosciences, 2021)
Serum and glucocorticoid-regulated kinase 1 (SGK1) is a Ser/Thr protein kinase involved in regulating cell survival, growth, proliferation and migration. Its elevated expression and dysfunction are reported in breast, prostate, hepatocellular, lung adenoma and renal carcinomas. We have analyzed the SGK1 mutations to explore their impact at the sequence and structure level by utilizing state-of-the-art computational approaches. Several pathogenic and destabilizing mutations were identified based on their impact on SGK1 and analyzed in detail. Three amino acid substitutions, K127M, T256A and Y298A, in the kinase domain of SGK1 were identified and incorporated structurally into original coordinates of SGK1 to explore their time evolution impact using all-atom molecular dynamic (MD) simulations for 200 ns. MD results indicate substantial conformational alterations in SGK1, thus its functional loss, particularly upon T256A mutation. This study provides meaningful insights into SGK1 dysfunction upon mutation, leading to disease progression, including cancer and neurodegeneration.